Strategi Pengembangan Usaha Madu Linot (Trigona Sp) di Desa Bitai Kecamatan Jaya Baru Kota Banda Aceh - maera ira (LPPM Universitas Malikussaleh - Indonesia, 2026)
This study aims to analyze the development strategy of the Madu Linot HJ business using a SWOT analysis approach. Research data were collected through interviews, observations, and questionnaires involving the business owner and consumers. The analysis was conducted using the IFE, EFE, and SWOT matrices. The IFE matrix analysis resulted in a total score of 4.00, indicating that the company’s internal position is very strong in leveraging its existing strengths. The EFE analysis produced scores ranging from 3.12 (consumer perception) to 3.90 (owner perception), reflecting the company’s excellent response to market opportunities. The SWOT quadrant mapping places Madu Linot HJ in Quadrant I (aggressive strategy), indicating a favorable growth position. Competitiveness improvement strategies focus on maximizing product quality advantages and managerial experience to exploit market opportunities. Recommended strategies include: (1) integration strategy through expanding distribution networks to pharmacies and supermarkets; (2) increasing market penetration through optimized digital promotion and educational content; (3) developing production capacity through modern cultivation techniques to minimize seasonal dependency; and (4) strengthening product legality through BPOM and Halal certification to address the threat of counterfeit honey. The implementation of these aggressive strategies is expected to sustainably strengthen the company’s competitive position in the non-timber forest products industry.